Predictors of Malignancy in Patients With Indeterminate Biliary Strictures and Atypical Biliary Cytology: Results From Retrospective Cohort Study. Issue 5 (18th March 2021) - Alali, Ali; Moris, Maria; Martel, Myriam; Streutker, Catherine; Cirocco, Maria; Mosko, Jeffrey; Kortan, Paul; Barkun, Alan; May, Gary R
Abstract: Background: Atypical cellular features are commonly encountered in patients with indeterminate biliary strictures, which are nondiagnostic of malignancy yet cannot rule it out. This study aims to identify clinical features that could discriminate patients with indeterminate biliary strictures and atypical biliary cytology who may harbor underlying malignancy. Methods: All patients with an indeterminate biliary stricture and an atypical brush cytology obtained during endoscopic brushings were identified in a large tertiary-care center. Demographical information, clinical data and the final pathological diagnosis were collected. The study cohort was divided based on the final diagnosis into benign and malignant groups. Descriptive and multivariable analyses were performed. Results: A total of 151 patients were included in the analysis. Of these, 62.9% were males with mean age of 61.7 ± 16.4 years. Overall, there was an almost equal distribution of patients in the benign and malignant groups. Older age (≥65 years), jaundice, weight loss, intrahepatic biliary and pancreatic duct dilation, double-duct sign and presence of a mass were associated with malignancy in the univariate analysis. However, only older age (odds ratio [OR] 1.02, 95% confidence interval [CI] 1.00 to 1.03), jaundice (OR 3.33, 95% CI 1.11 to 9.98) and presence of a mass (OR 12.10, 95% CI 4.94 to 29.67) were significantly associated with malignancy in the multivariate analysis. High CA19-9 was associated with malignancy only in patients with primary sclerosing cholangitis. Conclusion: In patients with indeterminate biliary stricture and atypical brush cytology, older age, jaundice and presence of a mass are significant predictors of malignancy. Patients with such characteristics need prompt evaluation to rule out underlying malignancy.